2020
DOI: 10.1101/2020.09.27.316018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Asymptomatic B-Cell, CD4+and CD8+T-Cell Epitopes, that are Highly Conserved Between Human and Animal Coronaviruses, Identified from SARS-CoV-2 as Immune Targets for Pre-Emptive Pan-Coronavirus Vaccines

Abstract: Over the last two decades, there have been three deadly human outbreaks of Coronaviruses (CoVs) caused by emerging zoonotic CoVs: SARS-CoV, MERS-CoV, and the latest highly transmissible and deadly SARS-CoV-2, which has caused the current COVID-19 global pandemic. All three deadly CoVs originated from bats, the natural hosts, and transmitted to humans via various intermediate animal reservoirs. Because there is currently no universal pan-Coronavirus vaccine available, two worst-case scenarios remain highly poss… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“… 9 T-cell epitopes were shown to be conserved between SARS-CoV-2 variants according to immunoinformatics analyses. 33-35 These factors might contribute to the high efficacy against severe–critical disease, hospitalization, and death in South Africa, where the relatively neutralization-resistant 20H/501Y.V2 variant predominates. 26 , 36…”
Section: Discussionmentioning
confidence: 99%
“… 9 T-cell epitopes were shown to be conserved between SARS-CoV-2 variants according to immunoinformatics analyses. 33-35 These factors might contribute to the high efficacy against severe–critical disease, hospitalization, and death in South Africa, where the relatively neutralization-resistant 20H/501Y.V2 variant predominates. 26 , 36…”
Section: Discussionmentioning
confidence: 99%
“…This study also reported recognition of newly defined HLA-I- and HLA-II-restricted T-cell epitopes by SARS-CoV-2-infected patients and SARS-CoV-2-seronegative subjects but none of our newly defined HLA-I restricted CTL epitopes was investigated in that study. Another recent study indicated that recognition of conserved CD4 epitopes within the SARS-CoV-2 sequence correlated with a less severe course of COVID, but not the overall frequency of SARS-CoV-2 specific CD8 + T-cells ( 12 ). Interestingly, they found that asymptomatic SARS-CoV-2 infected patients and healthy unexposed subjects showed a different pattern of recognized HLA-I-restricted T-cell epitopes than patients with a severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our study and the already available publications strongly suggest that SARS-CoV-2 reactive CD4 + and CD8 + T-cells are prevalent in a substantial proportion of subjects in the human populations, presumably induced by circulating common cold coronaviruses. A growing number of studies is indicating that the SARS-CoV-2-specific T-cells seem to be beneficial in patients with SARS-CoV-2 infection ( 4 , 6 9 , 12 , 34 ). Although it is suggestive, that such pre-existing beta-coronavirus cross-reactive T-cells could influence the susceptibility to SARS-CoV-2 or the severity of COVID-19, prospective studies are needed to investigate whether the presence of cross-reactive T-cells before the acquisition of SARS-CoV-2 indeed contributes to the striking variation of the clinical course of COVID-19 in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also discovered cross-reactive asymptomatic epitopes that induced strong B-cell and T-cell responses in “humanized” human leukocyte antigen (HLA)-Dr/HLA-A*02:01 double transgenic mice and recalled B-cell, CD4+, and CD8+ T-cell responses in both asymptomatic COVID-19 patients and healthy individuals who had never been exposed to SARS-CoV-2. The findings herein pave the way to develop a preemptive multiepitope pan-Coronavirus vaccine to protect against past, current, and potential future outbreaks ( Prakash et al, 2020 ).…”
Section: Introductionmentioning
confidence: 95%